Richter, Julia (2020): Translationshistoriographie. Perspektiven & Methoden. Wien: new academic press. - D'hulst, Lieven (chronotopos – A Journal of Translation History, 2022)
A book review of: Richter, Julia (2020): Translationshistoriographie. Perspektiven & Methoden. Wien: new academic press.